World watch geography 1 A geography course for grade 6 - Moorcroft, Christine (Karachi: Oxford university press, 2024)
"World Watch Geography Book 1" for Grade 6 introduces fundamental concepts of geography. It explores Earth's physical features, weather, climate, and basic ecosystems while touching on human settlements, resources, and their uses. The book aims to build foundational geographic skills and awareness of the relationship between humans and their environment.